Observations on selected variants of Fibonacci’s Liber Abaci - Carotenuto, Concetta (Reti Medievali Rivista, 2013)
This paper presents the proposed corrections to the vulgato text of Leonardo Pisano’s Liber Abaci. These corrections are based on the collation of some witnesses of the Teatry accomplished in view of his fist critical edition. We analyze, sometimes refuting their conclusions, previous philological studies on Teatry. We underline the difficulties experienced by philology in dealing with this matter. Accoedingly the initial state of the studies, the conclusions are provisional.